Propagador baseado em janela deslizante com formulação FDTD incondicionalmente estável de alta ordem - Claudio Garcia Batista (2012)
This work deals with electromagnetic wave propagation in the MF, HF, VHF and UHF bands (300 kHz to 3 GHz), motivated by the need for more accurate radio communication prediction for wireless networks planning. It is proposed an algorithm based on finite difference time domain(FDTD) and the concept of moving window to the develop an efficient FDTD Propagator for broadband applications. The formulation introduced here is based on three techniques for solving the problem: materialindependent PML formulation (MI-PML), unconditionally stable algorithm (US) and fourthorder accuracy in the Taylor series expansion for the spatial derivatives (FDTD(2,4) scheme). Thus, it is possible to use an unique formulation independent of the media configuration, exceedthe courant stability limit and to minimize the dispersion over long distances. The propagator computational implementation is built on the software SPRad (Sistema de Predição de Cobertura Radioelétrica), initially developed by the author in his master's work. The system is a platform for the radio propagation analysis where several methods can be used and compared on an integrated graphics user interface. The proposed formulation is validated with a canonical problem (scattering by a conducting cylinder) and its main characteristics are compared with other FDTD formulations, including the ADI (alternating direction implicit) method. The propagator is applied to terrains with canonical profiles (Gaussian hill and wedge) and the results are compared with integral equation methods found in the literature. The propagator applicability to the calculation of fields in refractive index dependent scenarios are verfied and compared with the SSPE method (Split Step Parabolic Equation). Finally, case studies involving measurements in Brasilia-DF and Denmark are analyzed.